Tracking metabolic gases in an airlift bioreactor for enhanced microalgae cultivation - Abdul Kadhim, Ghasaq H.; Al-Mashhadani, Mahmood K. H.; Hathal, Mustafa (Iraqi Journal of Chemical and Petroleum Engineering, 2025)
Airlift bioreactors have been classified as a promising technology for microalgae cultivation. Several improvements have contributed to increasing the mixing efficiency and production. However, some challenges are still facing this biological process. One challenge is the efficient dissolution and delivery of carbon dioxide to microalgae cells, which remains a limiting factor in the biological processes. On the other hand, sparging the gas in large quantities may lead to gas loss if microorganisms do not completely consume it. In this study, microalgae were cultivated in two stages and compared: the first stage of injecting 5 ml of carbon solution into a conical flask and the second stage of sparging 5 liters/hour in an airlift bioreactor with increasing sparging time this is done by sparging carbon dioxide gas at the same flow rate from day to day, but increasing the sparging time by 30 seconds, starting with sparging the gas for one minute until reaching 7 minutes. The results showed that the airlift bioreactor gives a higher growth rate of microalgae than that produced in a conical flask. The maximum biomass concentration reached 5 g/L in the airlift bioreactor culture with a maximum specific growth rate of 0.324 day−1, while it reached 1.0799 g/L in the conical flask culture with a specific growth rate of 0.187 day−1. This result shows the importance of the airlift bioreactor in microalgae cultivation. Also, the internal composition of the biomass was found that the airlift bioreactor was the best, as the amount of lipids, carbohydrates and protein was (2.06, 1.43, and 18.03 g per 30 g of dry biomass), respectively, while the internal composition of the control cultivation was (0.005386, 0.00428, 0.05754 and g/L), respectively. The volumetric mass transfer coefficient showed that when the sparging time increases, the oxygen gas transfer coefficient increases until it reaches 1.0397 s−1. The pH value was also maintained around 7, which is the appropriate value for increasing the growth rate.